Japanese Contractors in Overseas Markets Bridging Cultural and Communication Gaps - Suzuki, Kazuhito; Sui Pheng, Low (Management in the Built Environment,, 2019)
This book explores the differences in cultural attributes and management factors to enable managers working for Japanese contractors to reduce misunderstandings and misinterpretations when communicating with project team members from different cultural backgrounds. It focuses on Japanese contractors operating in Singapore, since the Singapore construction industry has, for many years, been one of the largest overseas construction markets for the top-5 Japanese contractors. Using Hofstede's national cultural framework for the cultural studies in construction project management, it reveals various real-world management practices and discusses national cultural differences relating to managers working for Japanese contractors in Singapore as well as the communication weaknesses of current management practices and styles. The results presented provide useful lessons for Japanese contractors operating in Singapore, as well as other parts of the world, to bridge culturaland communication gaps.